Job-Related Stress in Forensic Interviewers of Children with Use of Therapy Dogs Compared with Facility Dogs or No Dogs - Walsh, Diane; Yamamoto, Mariko; Willits, Neil H.; Hart, Lynette A. (Frontiers in Veterinary Science, 2018)
Sexually abused children providing essential testimony regarding crimes in forensic interviews now sometimes are provided facility dogs or therapy dogs for comfort. Facility dogs are extensively trained to work with forensic interviewers; when using therapy dogs in interviews, volunteers are the dog handlers. Interviews can impact child welfare workers’ mental health causing secondary traumatic stress (STS). To investigate this stress, first data were gathered on stress retrospectively for when interviewers initially started the job prior to working with a dog, and then currently, from forensic interviewers using a facility dog, a therapy or pet dog, or no dog. These retrospective and secondary traumatic stress scale (STSS) data compared job stress among interviewers of children using: a certified, workplace facility dog (n = 16), a volunteer’s trained therapy dog or the interviewer’s pet dog (n = 13/3), or no dog (n = 198). Retrospective scores of therapy dog and no dog interviewers’ stress were highest for the first interviewing year 1 and then declined. Extremely or very stressful retrospective scores differed among the three groups in year 1 (p < 0.038), and were significantly elevated for the therapy dog group as compared with the facility dog group (p < 0.035). All interviewing groups had elevated STSS scores; when compared with other healthcare groups that have been studied, sub-scores were especially high for Avoidance: a psychological coping mechanism to avoid dealing with a stressor. STSS scores differed among groups (p < 0.016), primarily due to Avoidance sub-scores (p < 0.009), reflecting higher Avoidance scores for therapy dog users than no dog users (p < 0.009). Facility dog users more consistently used dogs during interviews and conducted more interviews than therapy/pet dog users; both groups favored using dogs. Interviewers currently working with therapy dogs accompanied by their volunteers reported they had experienced heightened stress when they began their jobs; their high stress levels still persisted, indicating lower inherent coping skills and perhaps greater empathy among interviewers who later self-selected to work with therapy dogs. Results reveal extreme avoidant stress for interviewers witnessing children who are suffering and their differing coping approaches.